Effects of menopausal hormone therapy on gut microbiota in postmenopausal women and the relationship with bone metabolism - Xiong, Jieqi; Li, Lijun; Ao, Meihong; Tu, Yunxia; Tu, Kaijia; Li, Longyu (Frontiers in Medicine, 2025)
ObjectivesMenopausal Hormone Replacement Therapy (MHT) is widely used by peri- and post-menopausal women to alleviate menopause-related symptoms and preventing bone loss, but the underlying mechanisms remain inadequately elucidated. Accumulating evidence suggested that gut microbiota was involved in the regulation of bone metabolic processes. The aim of this study was to characterize the alterations in gut microbiota profiles by MHT treatment in postmenopausal women and explore the relationship between gut microbiota and bone metabolism.MethodsFecal samples collected from a total of 31 postmenopausal women with or without MHT were subjected to 16S ribosomal RNA (rRNA) gene sequencing and short-chain fatty acid (SCFAs) analysis in this study. The serum levels of bone metabolic markers were determined via chemiluminescent immunoassays. Spearman correlation coefficient was utilizes to assess the correlation between genera and bone metabolism indexes.ResultsPostmenopausal women undergoing MHT exhibited lower serum procollagen type I N propeptide (P1NP) and C-terminal telopeptide of type I collagen (CTX-1). Significant differences in alpha diversity and beta diversity were observed in the microbial compositions between two groups (P < 0.05). Of the total 295 microbial taxa identified, 16 taxa displayed significant differential abundance, with Coprococcus, Eubacterium_ruminantium_group, Lachnospiraceae_UCG-010 being more enriched in MHT+, correlating with lower bone metabolic markers and higher estrogen level. Conversely, Escherichia-Shigella taxa was more abundant in MHT- group, positively correlating with high bone metabolic markers and lower estrogen level. SCFAs appeared to have a limited role in bone metabolism but were found to be associated with several genera, including Coprococcus, Adlercreutzia, Colidextribacter.ConclusionsThe findings of the study demonstrated that MHT has the potential to prevent osteoporosis through the alteration of the gut microbial composition in postmenopausal women and identified promising microbial taxonomic that may contribute to the protective effects of MHT on bone mass conservation. Comparing with most previous studies that focused on the gut microbiota profiles between individuals with different bone mass, our study emphasized the protective role of gut microbiota in MHT process while bone mineral content (BMC) has no significant difference.